Pembuatan Sistem Informasi Administrasi di CV. Sinar Anugerah Perkasa - Stefanus Christian Gunawan; Djoni Haryadi Setiabudi; Rudy Adipranata (Jurnal Infra, 2019)
At this time the development of information systems was very rapid and unavoidable. And in this case the recording and bookkeeping of the company is done manually so that the accuracy and storage using handwriting will make it difficult for the company to carry out data collection and report preparation for the company. Based on the background of the problem, the author designed an administrative information system that can overcome these problems.The process of making this program is equipped with PHP as a programming language, bootstrap templates as a display of this program, Mysql Phpmyadmin as a database, sublime text 3 which is used to display programming language source code and web browsers as media to display results from sublime websites text 3.The results include adding, modifying, and deleting master data, purchasing processes, purchase orders, purchase returns, sales processes, sales returns, service processes, and stock card making used to store every transaction process that occurs in the company. . And also included the final report for the company calculating profit and loss and knowing the lane of purchases - sales to the company.